Smac Mimetic Compounds Engage Peripheral and Neuroimmune Action Against Glioblastoma - Malone, Kyle (Université d'Ottawa | University of Ottawa, 2024)
The Inhibitor of Apoptosis (IAP) proteins promote cell survival and are at the nexus of multiple inflammatory pathways. Smac mimetic compounds (SMCs) are small molecule drugs that inhibit the IAPs, sensitize cancer cells to TNFα-induced cell death, and alter NF-κB signaling to provide immunostimulation. SMCs are currently under evaluation as therapeutic agents against a wide array of cancers. We have previously shown that SMC combination with immunotherapies durably cures up to 40% of syngeneic, orthotopic murine glioblastoma (GBM) models. GBM is the commonest and deadliest primary brain tumor, with near uniformly fatal prognoses and no significant changes to standard of care in decades. Given key roles of IAPs in gliomagenesis and GBM therapy resistance, optimizing SMC-based therapies for GBM has significant potential for improving outcomes for this fatal cancer. Here, I aimed to identify and exploit resistance mechanisms to SMC-based immunotherapies for GBM. I show that GBM cells sensitive to SMC-mediated cell death remain sensitive under a diverse array of microenvironmental conditions. I further show that the central nervous system location limits primary immune responses against GBM, and that the tumor-associated macrophage (TAM) population represents a significant source of potential death ligands for GBM eradication. I elucidate a key role for astrocytes and TGFβ in GBM and TAM resistance to SMC treatment and show increasing dose of SMC and TGFβ blockade significantly improve efficacy of SMC-based immunotherapies. Further evaluating precise timing, delivery methods and other immunosuppressive targets for blockade will establish SMCs as potent immunostimulants promoting anti-GBM immunity. Collectively, SMCs can potently remodel the GBM microenvironment and provide significant immunostimulation allowing for enhancement of anti-GBM immunotherapies, thereby producing substantial survival benefit for this highly resistant and fatal cancer.
Keywords: Glioblastoma; Microglia; Glioma; Cell Death; Apoptosis; Inhibitor of Apoptosis; IAP; Astrocyte; Macrophage; Smac mimetic compound